No-Queue: Mobile Application for Virtual Queuing - Hashmillail, Syarafina (IRC, 2020)
Queuing theory includes all of our life's activities. We must wait in line whenever the server's server number or service rate does not match the rate the customers arrive in the queue. Whether it occurs at the supermarket checkout counter or accessing the Internet, the common concept of queueing exists whenever a large number of jobs or consumers need to enter a shared facility for operation. Queuing problems occur when the service does not match the level of demand. Queuing theory is the systematic study of this phenomenon in pursuit of discovering the optimal solution to this problem so that everyone will obtain service without waiting in line for a long time. Therefore, a mobile queuing application can be made possible where queuing can be accessible remotely, allow the monitoring of the waiting situation and can interact with system through mobile application. This paper suggests a solution to the problem of customer dissatisfaction with some services associated with long waiting times. It is a smart queue management system that provides real time visual and updates to service requests through a smartphone application in real time. Users acquire digital tickets and are free to leave the waiting area to be served until it is their turn. In order to increase user satisfaction, this software will use some feature and user acceptance testing.